Urban forest research in Malaysia: a systematic review - Rajoo, Keeren Sundara; Karam, Daljit Singh; Abdu, Arifin; Rosli, Zamri; Gerusu, Geoffery James (MDPI, 2021)
Sustainable urban development is a major issue in developing countries, namely in environmental and social aspects. Urban forests have the potential to address these issues. Thus, it is not surprising that urban forest research is slowly gaining traction in these regions. However, there have been limited urban forest research reviews focusing on developing countries, especially tropical countries in the global south. Research reviews are vital in identifying the distribution of research themes, hence revealing research gaps and needs. Therefore, this review paper aims to provide a deep insight into the development of urban forest research in Malaysia in the past 20 years. The core purpose of this review is to analyze the distribution of research themes in Malaysia, thus identifying research gaps and needs in developing countries. A total of 43 articles were selected for this review, using the PRISMA framework. The distribution of research articles showed a continuous increase over time, especially for the past five years (2016 to 2021). The reviewed articles were categorized according to five emerging research themes in urban forestry. More than 41% of the reviewed articles fell under Theme 1 (the physicality of urban forests), with the majority being on biodiversity (n = 10). Theme 5 (the governance of urban forest) had the lowest research output (n = 3). Urban forestry research is slowly gaining prominence globally including the global south; however, there are obvious preferences in research focus, causing some research questions to be neglected. These research gaps are especially evident in four areas—soil science, ecophysiology, valuation (economics), and environmental justice. These research gaps should be addressed by the scientific community to ensure a thorough and complete research growth pertaining to urban forestry.